The bigger the better? Predation and prey size choice in a patchy environment. Issue 2 (4th March 2022) - Vijayan, Sundararaj; Balaban-Feld, Jesse; Badichi, Shamir; Tamar Tov-Elem, Lotan; Kotler, Burt P.; Mitchell, William A.; Abramsky, Zvika
Abstract : Prey individuals vary in their body size even within groups and are often scattered heterogeneously in patchy environments. A foraging predator has to evaluate and select the patches where it can maximize its energetic gains. We studied the foraging behavior of a predator (little egret, Egretta garzetta ) hunting prey groups (goldfish, Carassius auratus ) that differed in body size and composition across three different patches (one large, one mixed, and one small). We quantified predator's stay time, return time and size-specific kills of the prey. The egret spent a similar amount of total time foraging in the three patches; however, it spent more time per-visit in pools containing large-bodied fish and also returned to those pools soonest after leaving to forage elsewhere, suggesting that the predators employ a time management strategy to maximize energetic returns. Furthermore, the egret preferentially killed larger individuals. Such size-selective predation can shift the prey size structure in the landscape and influence the dynamics of species interactions and eventually the structure of the communities.